Unseen Cinema - Picturing a Metropolis: New York City Unveiled Early American Avant-Garde Film 1894-1941 - Beheim, Eric; Sauer, Rodney; Sosin, Donald (image Entertainment, 2005)
The DVD depicts dynamic images of New York City and scenes of New Yorkers among the skyscrapers, streets, and night life of America's greatest city during a half century of progress, while at the same time showing changes in film style and the history of cinema experiments. Avant-garde moments pop up in the most unlikely of places including turn-of-the-twentieth-century actualities, commercial and radical newsreels, and Busby Berkeley's "Lullaby of Broadway" from "Gold Diggers of 1935". Included are spectacular prints of Charles Sheeler and Paul Strand's "Manhatta" (1921), Robert Flaherty's "Twenty-four-Dollar Island" (c. 1926), Robert Florey's "Skyscraper Symphony" (1929), Jay Leyda's "A Bronx Morning" (1931), and Rudy Burckhardt's "Pursuit of Happiness" (1940). [Cover]
Keywords: DVD-Video